2010
DOI: 10.1016/j.cell.2010.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Basal Dynamics of p53 Reveal Transcriptionally Attenuated Pulses in Cycling Cells

Abstract: Summary The tumor suppressor p53 is activated by stress and leads to cellular outcomes such as apoptosis and cell cycle arrest. Its activation must be highly sensitive to ensure that cells react appropriately to damage. However, proliferating cells often encounter transient damage during normal growth, where cell cycle arrest or apoptosis may be unfavorable. How does the p53 pathway achieve the right balance between high sensitivity and tolerance to intrinsic damage? Using quantitative time-lapse microscopy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
309
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(349 citation statements)
references
References 54 publications
40
309
0
Order By: Relevance
“…All potentially can generate bursts of activity, as in the p53 system (4,39). In analogy to our observations in Xenopus experiments, where the bursts changed in number but not shape in response to pathway inhibition, the p53 bursts are present in normally cycling cells and become more frequent with DNA damage (4).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…All potentially can generate bursts of activity, as in the p53 system (4,39). In analogy to our observations in Xenopus experiments, where the bursts changed in number but not shape in response to pathway inhibition, the p53 bursts are present in normally cycling cells and become more frequent with DNA damage (4).…”
Section: Discussionmentioning
confidence: 56%
“…Proper temporal control of pathway activity is crucial for normal development; however, the dynamic aspects of signaling are difficult to infer from population data and have lagged behind dissection of pathway components (2,3). The few cases that have been examined have revealed rich dynamics that could not have been predicted from knowledge of the molecular interactions or from bulk measurements of protein modifications or mRNA levels (2)(3)(4).…”
mentioning
confidence: 99%
“…There is accumulating evidence indicating that acetylation of p53 plays a major role in activating p53 function during stress responses (2,13,14). Following our early findings of C terminus p53 acetylation, we and others recently showed that p53 is also acetylated by Tip60 (also known as KAT5)/MOF (human ortholog of males absent on the first) at residue Lys120 (K120) within the DNA-binding domain (15)(16)(17).…”
mentioning
confidence: 99%
“…Images were acquired every 15 min for 12-24 h using the Nikon Elements software. Image analysis was performed with ImageJ (NIH) and Matlab (MathWorks) as described 33 .…”
Section: Live Cell Microscopymentioning
confidence: 99%